2018
DOI: 10.1186/s13633-018-0058-1
|View full text |Cite
|
Sign up to set email alerts
|

Mode of clinical presentation and delayed diagnosis of Turner syndrome: a single Centre UK study

Abstract: BackgroundEarly diagnosis of girls with Turner syndrome (TS) is essential to provide timely intervention and support. The screening guidelines for TS suggest karyotype evaluation in patients presenting with short stature, webbed neck, lymphoedema, coarctation of aorta or ≥ two dysmorphic features. The aim of the study was to determine the age and clinical features at the time of presentation and to identify potential delays in diagnosis of TS.MethodsRetrospective data on age at diagnosis, reason for karyotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
2
36
0
Order By: Relevance
“…The age at diagnosis for the patients in this study was similar to that found in the literature and was consistent with a recent study that has suggested a decline in the age at diagnosis over the last few years [6]. The presentation of TS varies throughout a patient' s life [7]. The most common complaints at the first presentation for TS are short stature and delay in puberty.…”
Section: Discussionsupporting
confidence: 90%
“…The age at diagnosis for the patients in this study was similar to that found in the literature and was consistent with a recent study that has suggested a decline in the age at diagnosis over the last few years [6]. The presentation of TS varies throughout a patient' s life [7]. The most common complaints at the first presentation for TS are short stature and delay in puberty.…”
Section: Discussionsupporting
confidence: 90%
“…In PATRO Children, the mean patient age at rhGH treatment initiation was 8.5 years (in treatment-naïve patients, who had mean baseline HSDS of −3.0). The diagnosis of TS is often delayed [27, 28], which could explain the late treatment initiation observed in PATRO Children. In one study of 81 TS patients, the mean (SD) delay in diagnosis was 7.7 (5.4) years in girls diagnosed in childhood or adolescence [28].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Turner syndrome should be strongly considered for any woman with unexplained growth failure or delayed puberty; lymphedema (edema of the hands or feet, nuchal fold, neck webbing, low hairline and hyperconvex or hypoplastic nails); characteristic facial features such as epicanthal folds, down‐slanting palpebral fissures, low‐set ears, and micrognathia; left‐sided cardiac anomalies, such as coarctation of the aorta, bicuspid aortic valve (BAV), and aortic stenosis; markedly elevated follicle‐stimulating hormone (FSH); infertility; cubitus valgus; multiple pigmented nevi; bone anomalies including short fourth metacarpal or metatarsal, Madelung deformity, and scoliosis; chronic otitis media and conductive or sensorineural hearing loss; or learning disabilities affecting visuospatial or nonverbal skills (Eckhauser, South, Meyers, Bleyl, & Botto, ; Gravholt, Andersen, et al, , section 1.3). Because Turner syndrome is still frequently diagnosed in adolescence or adulthood, clinicians should be aware that the most prominent signs and symptoms of Turner syndrome might change with age and maintain vigilance for prompt evaluation of women who meet these criteria (Apperley et al, ; Lee & Conway, ; Sävendahl & Davenport, ). Since many women may be detected as part of a fertility evaluation and discovered to have mosaicism, often at a low level, there are some adults with minimal external features.…”
Section: Geneticsmentioning
confidence: 99%